ANALYSIS OF URINE CYTOLOGY AT A COMMUNITY HOSPITAL - Mansoor, Ibrahim (Journal of Ayub Medical College Abbottabad, 2003)
Background: To review the pattern of urine cytology in our setting of a community hospital with age and gender distribution. Also to discuss the importance of this safe and inexpensive tool for diagnosing and screening urothelial cancers. We desire to encourage more wider and confident use of urine cytology in the routine practice. Method: We reviewed all the consecutive urine cytology specimens received at our institution during time frame of one year. The cytological diagnosis were grouped in four categories; 1: negative, benign or reactive cases; 2: cases showing acute inflammatory changes; 3: inconclusive cases and 4: malignant cases. Only the positive malignant cases were followed histologically to determine the accuracy and efficiency of urine cytological examination for positive cases. Results: A total of 1957 consecutive urine cytology specimens were reviewed. Majority of the cases were negative for tumour (67.19%). The most common diagnostic category was acute inflammatory case (17.3%) while inconclusive cases constituted 11.39% of total. There were 23 (1.18%) positive cases that were diagnosed malignant on urine cytology. These 23 malignant cases were followed histologically and 22 (95.6%) cases turned out to be malignant. Conclusion: Urine cytological examination is an efficient tool that has a good diagnostic yield in detecting malignant urothelial lesions. It should be used routinely for diagnosing, screening and for follow-up of all malignant urothelial lesions. Keywords: Urine cytology, urothelial neoplasm.